2021
DOI: 10.1002/ppul.25278
|View full text |Cite
|
Sign up to set email alerts
|

Congenital central hypoventilation syndrome and ventilatory responses during cardiopulmonary exercise testing

Abstract: Background: Previous studies have shown evidence of hypoxemia and hypercapnia during cardiopulmonary exercise test (CPET) evaluation in children with congenital central hypoventilation syndrome (CCHS). However, there are no longitudinal studies which compared CPET findings to polysomnogram (PSG) or PHOX2B mutation, to date.Objectives: To describe the longitudinal CPET findings in a cohort of children with CCHS and correlate the findings to the PSG results.Methods: This retrospective study was conducted in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In our study, most (93%) patients exercised and participated in mainstream PE without restrictions, including moderate to strenuous exercise without experiencing any symptoms. The results of our study and prior studies showing gas exchange abnormalities with exercise suggests that monitoring SpO 2 and ETCO 2 during exercise should be strongly considered and an individualized exercise plan should be formulated 3–6 . Paton et al and Hager et al showed that CCHS patients increased minute ventilation during exercise, but to a lesser extent than controls 3,5 .…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…In our study, most (93%) patients exercised and participated in mainstream PE without restrictions, including moderate to strenuous exercise without experiencing any symptoms. The results of our study and prior studies showing gas exchange abnormalities with exercise suggests that monitoring SpO 2 and ETCO 2 during exercise should be strongly considered and an individualized exercise plan should be formulated 3–6 . Paton et al and Hager et al showed that CCHS patients increased minute ventilation during exercise, but to a lesser extent than controls 3,5 .…”
Section: Discussionsupporting
confidence: 59%
“…There is limited literature on PHOX2B genotype−phenotype correlation for ventilatory disturbances during exercise. A retrospective study of nine patients with CCHS—four with PARM and five with NPARM—requiring nocturnal NPPV identified higher ETCO 2 in patients with PARMs at peak exercise during a cycle cardiopulmonary exercise test 4 . During the 6MWT, we found a significant difference between the peak ETCO 2 and nadir SpO 2 between the three PHOX2B genotype groups.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations